Polyvinyl Acetal Resin
Patent Information
- Application Number
- JP2024092310
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-06-06
- Publication Date
- 2025-02-27
- Estimated Expiration
- 2044-05-22
AI Technical Summary
【0054】 本発明によれば、機械的強度が高く、好適な表面粗さを有するセラミックグリーンシートを得ることができ、信頼性に優れた積層セラミックコンデンサを作製可能なポリビニルアセタール樹脂、セラミックグリーンシート用スラリー、セラミックグリーンシート及び積層セラミックコンデンサを提供することができる。
Smart Images

Figure 0007637303000003 
Figure 0007637303000001 
Figure 0007637303000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyvinyl acetal resin, a slurry for a ceramic green sheet, a ceramic green sheet, and a multilayer ceramic capacitor. [Background technology]
[0002] 2. Description of the Related Art In recent years, electronic components mounted in various electronic devices have become smaller and more laminated, and laminated electronic components such as multilayer circuit boards, laminated coils, and laminated ceramic capacitors are widely used. Among them, multilayer ceramic capacitors are generally manufactured through the following steps. First, a plasticizer, a dispersant, etc. are added to a solution in which a binder resin such as polyvinyl butyral resin or poly(meth)acrylic acid ester resin is dissolved in an organic solvent, and then a ceramic raw material powder is added and mixed uniformly with a mixing device such as a bead mill or a ball mill to obtain a ceramic slurry composition having a certain viscosity after defoaming. This slurry composition is cast onto a support surface such as a release-treated polyethylene terephthalate film or a SUS plate using a doctor blade, reverse roll coater, etc., and the volatile matter such as the solvent is distilled off by heating, etc., and then peeled off from the support to obtain a ceramic green sheet. Next, a conductive paste that will become the internal electrodes is applied to the obtained ceramic green sheets by screen printing, and multiple sheets are alternately stacked and heated and pressed to produce a laminate. After that, a process to thermally decompose and remove the binder resin components and the like contained in the laminate, that is, a so-called degreasing process, is performed, and external electrodes are sintered onto the end faces of the ceramic sintered body obtained by firing to obtain a multilayer ceramic capacitor.
[0003] For example, Patent Document 1 describes a polyvinyl acetal resin suitable as a ceramic binder, which has a specified degree of polymerization, vinyl ester unit content, and degree of acetalization, and in which the molar ratio of the portion acetalized with acetaldehyde to the portion acetalized with butylaldehyde is within a specified range. Furthermore, Patent Document 2 describes a polyvinyl acetal resin having a specific degree of polymerization, a vinyl ester unit content, and a degree of acetalization, and having specific structural units. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2011-236304 A [Patent Document 2] International Publication No. 2012 / 023517 Summary of the Invention [Problem to be solved by the invention]
[0005] Meanwhile, in recent years, with the trend toward greater functionality and smaller size of electronic devices, multilayer ceramic capacitors are being demanded to have larger capacitance and smaller size, and ceramic green sheets are being demanded to be even thinner. However, when the polyvinyl acetal resins described in Patent Documents 1 and 2 are used, there is a problem that the strength of the obtained ceramic green sheet is insufficient. There is also a problem that the surface roughness of the resulting ceramic green sheet decreases.
[0006] The present invention aims to provide a polyvinyl acetal resin capable of producing a ceramic green sheet having high mechanical strength and suitable surface roughness and capable of producing a multilayer ceramic capacitor with excellent reliability, and to provide a ceramic green sheet slurry, a ceramic green sheet, and a multilayer ceramic capacitor using the polyvinyl acetal resin. [Means for solving the problem]
[0007] The present disclosure 1 relates to a polymer having a z-average molecular weight (THFMz) obtained by using THF as a mobile phase in a GPC measurement using a differential refractive index detector, and a z-average molecular weight (NMPMz) obtained by using NMP as a mobile phase, which satisfy the following formula (1); and in an IR absorption spectrum measured by an infrared spectrophotometer, the z-average molecular weight satisfies a wavenumber of 3050 to 3750 cm -1 When the minimum transmittance of the peak within the range is X (%), among the wave numbers showing the transmittance a (%) that satisfies [100-(100-X) / 2], the wave number on the low wave number side is A and the wave number on the high wave number side is B. 1 The polyvinyl acetal resin has a hydroxyl group amount converted wavenumber width of 8.3 to 9.4, which is calculated using the amount of hydroxyl groups measured by 1 H-NMR and is calculated using the following formula (2): THFMz-NMPMz<470000 (1) Hydroxyl group amount conversion wave number width (cm -1 / mol%)=[(BA) / hydroxyl group amount] (2) In the present disclosure 2, the A is 3275 cm -1 Above, 3305cm -1 The polyvinyl acetal resin according to the present disclosure is as follows: Disclosure 3 relates to the above A, B and 1 The polyvinyl acetal resin according to Disclosure 1 or 2 has a hydroxyl group-acetal group amount converted wavenumber width of 0.120 to 0.135, which is calculated by the following formula (3) using the hydroxyl group amount and acetal group amount measured by H-NMR: Hydroxyl group Acetal group amount conversion wave number width (cm -1 / mol% / mol%)=[(BA) / amount of hydroxyl groups / amount of acetal groups] (3) Disclosure 4 is a polyvinyl acetal resin according to any one of Disclosures 1 to 3, wherein a 5 mass % solution of the polyvinyl acetal resin in a 1:1 mixed solvent of ethanol and toluene has a solution viscosity of 64 mPa s or more and 2,000 mPa s or less, as measured using a B-type viscometer at a solution temperature of 20°C. The present disclosure 5 is the polyvinyl acetal resin according to any one of the present disclosures 1 to 4, wherein the amount of hydroxyl groups is 18 mol % or more and 40 mol % or less. The present disclosure 6 is the polyvinyl acetal resin according to any one of the present disclosures 1 to 5, in which the amount of acetyl groups is 0.1 mol % or more and 20 mol % or less. The present disclosure 7 is a slurry for a ceramic green sheet, comprising the polyvinyl acetal resin according to any one of the present disclosures 1 to 6, an organic solvent, and ceramic powder. The eighth aspect of the present disclosure is a ceramic green sheet obtained by using the slurry for the ceramic green sheet according to the seventh aspect of the present disclosure. The ninth aspect of the present disclosure is a multilayer ceramic capacitor obtained by using the ceramic green sheet according to the eighth aspect of the present disclosure. The present invention will be described in detail below.
[0008] As a result of intensive research, the present inventors have found that the z-average molecular weight measured by changing the solvent of the mobile phase satisfies a predetermined relationship, and the IR absorption spectrum measured by an infrared spectrophotometer has a wavelength of 3050 to 3750 cm -1 The inventors have found that a polyvinyl acetal resin having a peak wavenumber width within a predetermined range has high mechanical strength, can give a ceramic green sheet having a suitable surface roughness, and can fabricate a multilayer ceramic capacitor with excellent reliability, and have completed the present invention.
[0009] The polyvinyl acetal resin of the present invention has a z-average molecular weight (THFMz) obtained by using THF as a mobile phase in GPC measurement using a differential refractive index detector, and a z-average molecular weight (NMPMz) obtained by using NMP as a mobile phase, which satisfy the following formula (1); and has an IR absorption spectrum measured by an infrared spectrophotometer, which has a wave number of 3050 to 3750 cm -1 When the minimum transmittance of the peak within the range is X (%), among the wave numbers showing the transmittance a (%) that satisfies [100-(100-X) / 2], the wave number on the low wave number side is A and the wave number on the high wave number side is B. 1The hydroxyl group amount converted wavenumber width calculated by the following formula (2) using the hydroxyl group amount measured by 1 H-NMR is 8.3 to 9.4. THFMz-NMPMz<470000 (1) Hydroxyl group amount conversion wave number width (cm -1 / mol%)=[(BA) / hydroxyl group amount] (2) By using such a polyvinyl acetal resin, it is possible to obtain a ceramic green sheet having high strength and suitable surface roughness.
[0010] The polyvinyl acetal resin of the present invention has a z-average molecular weight (THFMz) and a z-average molecular weight (NMPMz) that satisfy the above formula (1) in GPC measurement using a differential refractive index detector. By setting the molecular weight within the above range, the variation in molecular weight can be narrowed, and the surface roughness of the ceramic green sheet can be reduced. The THFMz-NMPMz is preferably 100 or more, more preferably 1000 or more, and is preferably less than 470,000, more preferably less than 450,000. In the present invention, THFMz-NMPMz serves as an index of the narrowness of the variation in apparent molecular weight due to hydrogen bonding. The above-mentioned THFMz-NMPMz can be calculated by measuring the z-average molecular weight (THFMz) obtained by gel permeation chromatography (GPC) measurement using tetrahydrofuran as the mobile phase and solvent and a refractive index detector as the detector, using THF as the mobile phase, and then measuring the z-average molecular weight (NMPMz) obtained by GPC measurement using N-methylpyrrolidone as the mobile phase and solvent and a refractive index detector as the detector, using NMP as the mobile phase, and calculating THFMz-NMPMz. The column used for the measurement of THFMz may be TSKgel SuperHZM-H (manufactured by Tosoh Corporation), and the column used for the measurement of NMPMz may be LF-804 (manufactured by Shodex Corporation), or the like.
[0011] The polyvinyl acetal resin of the present invention preferably has a z-average molecular weight (THFMz) obtained by using THF as a mobile phase of 300,000 or more and 2,000,000 or less. By setting it within the above range, the variation in strength of the ceramic green sheet can be suppressed. The THFMz is more preferably 400,000 or more and more preferably 1,200,000 or less.
[0012] The polyvinyl acetal resin of the present invention preferably has a z-average molecular weight (NMPMz) obtained by using NMP as a mobile phase of 300,000 or more and 1,500,000 or less. By setting it within the above range, the variation of the ceramic green sheet can be suppressed. The NMPMz is more preferably 400,000 or more, and more preferably 1,000,000 or less.
[0013] The above-mentioned THFMz-NMPMz can be adjusted, for example, by changing the average degree of polymerization and degree of saponification of the raw material polyvinyl alcohol resin, and the temperature and time conditions of the acetalization reaction, and by appropriately setting the amount of acetal groups, hydroxyl groups, acetyl groups, etc. of the polyvinyl acetal resin. In particular, the above-mentioned THFMz-NMPMz can be adjusted by changing the cooling temperature, cooling time, reaction temperature, reaction time, holding (aging) temperature, and holding (aging) time during the acetalization reaction described below, and in particular by changing the reaction temperature, reaction time, cooling temperature, and cooling time.
[0014] The polyvinyl acetal resin of the present invention has an IR absorption spectrum measured by an infrared spectrophotometer having a wave number of 3050 to 3750 cm -1 When the minimum transmittance of the peak within the range is X (%), among the wave numbers showing the transmittance a (%) that satisfies [100-(100-X) / 2], the wave number on the low wave number side is A and the wave number on the high wave number side is B. 1 The hydroxyl group amount converted wavenumber width calculated from the above formula (2) using the hydroxyl group amount measured by 1 H-NMR is 8.3 to 9.4. By setting the content within the above range, the strength of the ceramic green sheet can be improved. The lower limit of the wavenumber width is preferably 8.3, more preferably 8.35, and the upper limit of the wavenumber width is preferably 9.4, more preferably 9.35. In the present invention, the wave number width is an index of the amount of hydrogen bonds between resins. The IR absorption spectrum can be measured by a transmission method using a Fourier transform infrared spectrophotometer (such as HORIBA's "FT-720" or JASCO's "FT / IR-4000") at 20°C.
[0015] The polyvinyl acetal resin of the present invention is 1 Using the hydroxyl group amount and acetal group amount measured by 1 H-NMR, the hydroxyl group-acetal group amount converted wave number width calculated by the above formula (3) is preferably 0.120 to 0.135. By setting the content within the above range, the strength of the ceramic green sheet can be improved. The lower limit of the hydroxyl group-acetal group amount converted wave number width is more preferably 0.122, and even more preferably 0.123, and the upper limit thereof is more preferably 0.134, and even more preferably 0.133.
[0016] In the analysis of polyvinyl acetal resin using the above infrared spectrophotometer, the spectrum originating from the stretching vibration of the CH bond of polyvinyl acetal resin was observed at 2980 cm -1 The above peak analysis shows that the minimum transmittance of the peak due to the stretching vibration of the C-H bond is around 2500 cm -1 and 3050cm -1 The film thickness of the measurement sample is adjusted so that it is 20% of the baseline when the line connecting the lines is connected. Furthermore, the measurement results show that the wavenumber of 3050 to 3750 cm -1 A baseline is drawn for peaks that appear within this range, and the data is corrected so that the transmittance at both ends of the peak is 100%.
[0017] An example of an IR absorption spectrum of the polyvinyl acetal resin of the present invention measured by an infrared spectrophotometer at 20° C. is shown in Fig. 1. In Fig. 1, the vertical axis represents transmittance and the horizontal axis represents wave number. In the IR absorption spectrum shown in FIG. 1, the minimum transmittance X is 65.7%. The transmittance a that satisfies [100-(100-X) / 2] is 82.85%, and the wavenumber A on the low wavenumber side is 3297 cm -1 , the wave number B on the high wave number side is 3557 cm -1 In the above case, if the amount of hydroxyl groups is 30 mol%, the hydroxyl group amount converted wave number width [(BA) / amount of hydroxyl groups] is 8.67 (cm -1 / mol%). The above wave number A is 3275 cm -1 More than 3280cm is preferable. -1 More than 3305cm is more preferable. -1 Less than 3300cm is preferable. -1 The following is preferred: The wave number B is 3530 cm -1 More than 3550cm is preferable. -1 More than 3600cm is preferable. -1 The following is preferable: 3580cm -1 The following is preferred: The transmittance a is preferably 80% or more and 85% or less.
[0018] The wavenumber width can be adjusted, for example, by changing the average degree of polymerization and degree of saponification of the raw material polyvinyl alcohol resin, and the temperature and time conditions of the acetalization reaction, and by appropriately setting the amount of acetal groups, hydroxyl groups, acetyl groups, etc. of the polyvinyl acetal resin. The wavenumber width can be adjusted by changing the cooling temperature, cooling time, cooling rate, heating rate, reaction temperature, reaction time, holding (aging) temperature, and holding (aging) time during the acetalization reaction described below, and in particular can be adjusted by changing the cooling temperature and cooling time.
[0019] The polyvinyl acetal resin of the present invention preferably has a solution viscosity of 64 mPa s or more and 2,000 mPa s or less, when a 5% by mass solution of the polyvinyl acetal resin in a 1:1 mixed solvent of ethanol and toluene is measured using a B-type viscometer at a solution temperature of 20°C. In order to improve the tensile strength, the viscosity is more preferably 64 mPa s or more, and even more preferably 65 mPa s or more. In order to improve the viscosity stability of the ceramic slurry composition, the viscosity is more preferably 2000 mPa s or less, and even more preferably 1800 mPa s or less. The above-mentioned B-type viscometer may be, for example, a TVB-10 viscometer manufactured by Toki Sangyo Co., Ltd. In addition, the rotor and rotation speed during viscosity measurement are preferably adjusted appropriately depending on the solution viscosity, and for example, it is preferable to measure using SPINDLE No. M1 to M4 at a rotation speed in the range of 0.3 to 100 rpm.
[0020] The viscosity can be adjusted, for example, by changing the average degree of polymerization and degree of saponification of the raw material polyvinyl alcohol resin, and the temperature and time conditions of the acetalization reaction, and by appropriately setting the amount of acetal groups, hydroxyl groups, acetyl groups, etc. of the polyvinyl acetal resin.
[0021] The polyvinyl acetal resin of the present invention preferably has a structural unit having an acetal group represented by the following formula (4), a structural unit having a hydroxyl group represented by the following formula (5), and a structural unit having an acetyl group represented by the following formula (6).
[0022] [ka] In the above formula (4), R 1 represents a hydrogen atom or an alkyl group having 1 to 20 carbon atoms.
[0023] In the above formula (4), R 1When is an alkyl group having 1 to 20 carbon atoms, examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a pentyl group, a hexyl group, a heptyl group, a 2-ethylhexyl group, an octyl group, a nonyl group, a decyl group, an undecyl group, a dodecyl group, a tridecyl group, a tetradecyl group, a pentadecyl group, an octadecyl group, etc. Among these, a methyl group and an n-propyl group are preferable.
[0024] In the polyvinyl acetal resin of the present invention, the content of the structural unit having the acetal group represented by the above formula (4) (hereinafter also referred to as the "acetal group amount") is preferably 50 mol % in lower limit and 83 mol % in upper limit. When the amount of acetal groups is 50 mol % or more, the solubility in organic solvents can be improved, and when the amount of acetal groups is 83 mol % or less, the polyvinyl acetal resin can have excellent tensile strength. The acetal group amount is more preferably 55 mol % in lower limit and 80 mol % in upper limit, that is, the acetal group amount is preferably 50 to 83 mol %, and more preferably 55 to 80 mol %. By setting the hydroxyl group amount within the above range, the wave number width in terms of the hydroxyl group amount / acetal group amount can be set within a predetermined range. The amount of acetal groups is, for example, 1 It can be measured by H-NMR. Regarding the method for calculating the amount of acetal groups, since the acetal groups of polyvinyl acetal resin are obtained by acetalizing two hydroxyl groups of polyvinyl alcohol, the method of counting the two acetalized hydroxyl groups is used.
[0025] In the polyvinyl acetal resin of the present invention, the content of the structural unit having a hydroxyl group represented by the above general formula (5) (hereinafter also referred to as the "hydroxyl group amount") is preferably 18 mol % in lower limit and 40 mol % in upper limit. When the amount of hydroxyl groups is 18 mol % or more, the polyvinyl acetal resin can have high toughness, and when the amount of hydroxyl groups is 40 mol % or less, the solubility in organic solvents can be sufficiently improved. The lower limit of the hydroxyl group amount is more preferably 22 mol % and the upper limit is more preferably 38 mol %. That is, the hydroxyl group amount is preferably 18 to 40 mol %, and more preferably 22 to 38 mol %. By setting the hydroxyl group amount within the above range, the hydroxyl group amount converted wave number width and the hydroxyl group amount converted wave number width in acetal group amount can be set within a predetermined range. The amount of hydroxyl groups is, for example, 1 It can be measured by H-NMR.
[0026] In the polyvinyl acetal resin of the present invention, the content of the structural unit having an acetyl group represented by the above general formula (6) (hereinafter also referred to as the "acetyl group amount") is preferably 0.1 mol % in lower limit and 20.0 mol % in upper limit. When the amount of acetyl groups is 0.1 mol% or more, the increase in viscosity of the slurry composition for ceramic green sheets due to intramolecular and intermolecular hydrogen bonds of hydroxyl groups in the polyvinyl acetal resin can be suppressed.When the amount of acetyl groups is 20.0 mol% or less, the flexibility of the polyvinyl acetal resin is not excessively increased, and the handleability can be improved. The lower limit of the acetyl group amount is more preferably 0.5 mol % and the upper limit is more preferably 18.0 mol %. That is, the acetyl group amount is preferably 0.1 to 20.0 mol %, and more preferably 0.5 to 18.0 mol %. The amount of acetyl groups is, for example, 1 It can be measured by H-NMR.
[0027] In the polyvinyl acetal resin of the present invention, from the viewpoint of maintaining mechanical strength when a thin film ceramic green sheet is produced, the average polymerization degree has a preferable lower limit of 500, more preferably 600, and from the viewpoint of solubility in organic solvents and dissolution viscosity, the average polymerization degree is preferably 10,000, more preferably 9,000. That is, the average polymerization degree is preferably 500 to 10,000, more preferably 600 to 9,000. The average degree of polymerization of the polyvinyl acetal resin is the same as that of the raw material polyvinyl alcohol, and can be measured in accordance with JIS K 6726.
[0028] The polyvinyl acetal resin of the present invention can usually be produced by acetalizing a polyvinyl alcohol resin.
[0029] As the polyvinyl alcohol resin, for example, a conventionally known polyvinyl alcohol resin such as a resin produced by saponifying a polyvinyl acetate resin with an alkali, an acid, aqueous ammonia or the like can be used. The polyvinyl alcohol resin may be fully saponified, but it does not need to be fully saponified as long as there is at least one unit having two consecutive hydroxyl groups at the meso and racemo positions at at least one position in the main chain, and may be a partially saponified polyvinyl alcohol resin. In addition, as the polyvinyl alcohol resin, a copolymer of vinyl alcohol and a monomer copolymerizable with vinyl alcohol, such as an ethylene-vinyl alcohol copolymer resin or a partially saponified ethylene-vinyl alcohol copolymer resin, may also be used. The polyvinyl acetate resin may be, for example, an ethylene-vinyl acetate copolymer.
[0030] The polyvinyl alcohol resin preferably has a degree of saponification of 75 mol % or more. The saponification degree is preferably 76 mol % or more and 99.9 mol % or less, and more preferably 78 mol % or more and 99.5 mol % or less. That is, the saponification degree is preferably 76 to 99.9 mol %, and more preferably 78 to 99.5 mol %.
[0031] The above acetalization is preferably carried out in a water solvent, in a mixed solvent of water and an organic solvent compatible with water, or in an organic solvent. As the organic solvent compatible with water, for example, an alcohol-based organic solvent can be used. Examples of the organic solvent include alcohol-based organic solvents, aromatic organic solvents, aliphatic ester-based solvents, ketone-based solvents, lower paraffin-based solvents, ether-based solvents, amide-based solvents, and amine-based solvents. Examples of the alcohol-based organic solvent include methanol, ethanol, n-propanol, isopropanol, n-butanol, and tert-butanol. Examples of the aromatic organic solvent include xylene, toluene, ethylbenzene, and methyl benzoate. Examples of the aliphatic ester solvent include methyl acetate, ethyl acetate, butyl acetate, methyl propionate, ethyl propionate, methyl butyrate, ethyl butyrate, methyl acetoacetate, and ethyl acetoacetate. Examples of the ketone solvent include acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, methylcyclohexanone, benzophenone, and acetophenone. Examples of the lower paraffin solvent include hexane, pentane, octane, cyclohexane, and decane. Examples of the ether solvent include diethyl ether, tetrahydrofuran, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, and propylene glycol diethyl ether. Examples of the amide solvent include N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and acetanilide. Examples of the amine solvent include ammonia, trimethylamine, triethylamine, n-butylamine, di-n-butylamine, tri-n-butylamine, aniline, N-methylaniline, N,N-dimethylaniline, and pyridine. These solvents may be used alone or in combination of two or more. Among these, ethanol, n-propanol, isopropanol, and tetrahydrofuran are particularly preferred from the viewpoints of solubility in the resin and ease of purification.
[0032] The acetalization is preferably carried out in the presence of an acid catalyst. The acid catalyst is not particularly limited, and examples thereof include mineral acids such as sulfuric acid, hydrochloric acid, nitric acid, and phosphoric acid, carboxylic acids such as formic acid, acetic acid, and propionic acid, and sulfonic acids such as methanesulfonic acid, ethanesulfonic acid, benzenesulfonic acid, and paratoluenesulfonic acid. These acid catalysts may be used alone or in combination of two or more compounds. Among them, hydrochloric acid, nitric acid, and sulfuric acid are preferred, and hydrochloric acid is particularly preferred.
[0033] The aldehyde used in the acetalization reaction may be an aldehyde having a chain aliphatic group, a cyclic aliphatic group, or an aromatic group having 1 to 10 carbon atoms. Any known aldehyde may be used as the aldehyde. The aldehyde used in the acetalization reaction is not particularly limited, and may be, for example, an aliphatic aldehyde, an aromatic aldehyde, or the like. Examples of the aliphatic aldehyde include formaldehyde, acetaldehyde, propionaldehyde, n-butyraldehyde, isobutyraldehyde, n-valeraldehyde, n-hexylaldehyde, 2-ethylbutyraldehyde, 2-ethylhexylaldehyde, n-heptylaldehyde, n-octylaldehyde, n-nonylaldehyde, n-decylaldehyde, and amylaldehyde. Examples of the aromatic aldehyde include benzaldehyde, cinnamaldehyde, 2-methylbenzaldehyde, 3-methylbenzaldehyde, 4-methylbenzaldehyde, p-hydroxybenzaldehyde, m-hydroxybenzaldehyde, phenylacetaldehyde, and β-phenylpropionaldehyde. These aldehydes may be used alone or in combination of two or more. Among them, preferred aldehydes are formaldehyde, acetaldehyde, butylaldehyde, 2-ethylhexylaldehyde, and n-nonylaldehyde, which have excellent acetalization reactivity and can provide sufficient internal plasticizing effect to the resin produced, thereby imparting good flexibility. In addition, more preferred are formaldehyde, acetaldehyde, and butylaldehyde, which can provide an adhesive composition that is particularly excellent in impact resistance and adhesion to metals.
[0034] The amount of the aldehyde to be added can be appropriately set according to the amount of acetal groups in the target polyvinyl acetal resin. In particular, it is preferable to add 50 mol% or more and 95 mol% or less, more preferably 55 mol% or more and 90 mol% or less, based on 100 mol% of polyvinyl alcohol, because this allows the acetalization reaction to proceed efficiently and makes it easy to remove unreacted aldehyde.
[0035] The acetalization reaction is preferably carried out by lowering the temperature to a predetermined temperature and maintaining it thereat (cooling step), and then raising the temperature to a predetermined temperature and maintaining it thereat (reaction step). The cooling time in the cooling step is preferably 30 minutes or more and 5 hours or less, and more preferably 1 hour or more and 3 hours or less. The cooling temperature in the cooling step is preferably 8°C or higher and 20°C or lower, and more preferably 10°C or higher and 17°C or lower. Furthermore, the cooling rate is preferably 0.2° C. / min or more and 3° C. / min or less, and more preferably 0.5° C. / min or more and 2° C. / min or less. By setting the cooling time and cooling temperature as described above, the wave number width can be set within a predetermined range.
[0036] The reaction time in the above reaction step is preferably 1 hour or more and 12 hours or less, and more preferably 2 hours or more and 6 hours or less. The reaction temperature in the above reaction step is preferably 47°C or higher and 58°C or lower, and more preferably 50°C or higher and 55°C or lower. The temperature rise rate is preferably 0.05° C. / min or more and 1.5° C. / min or less, and more preferably 0.1° C. / min or more and 1° C. / min or less. By setting the reaction time and reaction temperature as described above, the amount of THFMz-NMPMz can be kept within a predetermined range.
[0037] By containing the polyvinyl acetal resin of the present invention and a plasticizer, a resin composition for a ceramic green sheet can be obtained. The resin composition for a ceramic green sheet may contain components such as an antioxidant, a surfactant, an ultraviolet absorber, and a defoaming agent, so long as the effects of the present invention are not adversely affected.
[0038] As a method for producing the resin composition for ceramic green sheets, for example, a plasticizer and other additives added as necessary are added to a polyvinyl acetal resin obtained by acetalizing a polyvinyl alcohol resin with an aldehyde, and then mixed to obtain a resin composition for ceramic green sheets.
[0039] The resin composition for a ceramic green sheet contains a plasticizer. By adding the plasticizer, the mechanical strength and flexibility of the resulting ceramic green sheet can be significantly improved. Examples of the plasticizer include phthalic acid diesters such as dioctyl phthalate (DOP) and dibutyl phthalate (DBP), adipic acid diesters such as dioctyl adipate, and alkylene glycol diesters such as triethylene glycol-di-2-ethylhexanoate, tetraethylene glycol-di-2-ethylhexanoate, triethylene glycol-di-2-ethylbutyrate, tetraethylene glycol-di-2-ethylbutyrate, tetraethylene glycol-di-heptanoate, and triethylene glycol-di-heptanoate.
[0040] In the resin composition for ceramic green sheets, the content of the plasticizer relative to 100 parts by weight of the polyvinyl acetal resin is preferably 7 parts by weight in lower limit, more preferably 8.5 parts by weight in lower limit, preferably 18 parts by weight in upper limit, more preferably 13.5 parts by weight in upper limit.
[0041] A slurry for ceramic green sheets can be prepared by mixing the polyvinyl acetal resin of the present invention with an organic solvent and ceramic powder.
[0042] The organic solvent is not particularly limited, and may be any solvent capable of dissolving the polyvinyl acetal resin, such as ketones, including acetone, methyl ethyl ketone, dipropyl ketone, and diisobutyl ketone. Other examples include alcohols, such as methanol, ethanol, isopropanol, and butanol, and aromatic hydrocarbons, such as toluene and xylene. Other examples include esters, such as methyl propionate, ethyl propionate, butyl propionate, methyl butanoate, ethyl butanoate, butyl butanoate, methyl pentanoate, ethyl pentanoate, butyl pentanoate, methyl hexanoate, ethyl hexanoate, butyl hexanoate, 2-ethylhexyl acetate, and 2-ethylhexyl butyrate. Other examples include methyl cellosolve, ethyl cellosolve, butyl cellosolve, terpineol, dihydroterpineol, butyl cellosolve acetate, butyl carbitol acetate, terpineol acetate, and dihydroterpineol acetate. In particular, alcohols, ketones, aromatic hydrocarbons and mixed solvents thereof are preferred in terms of coating and drying properties, with a mixed solvent of ethanol and toluene and a mixed solvent of methyl ethyl ketone and toluene being more preferred.
[0043] The content of the organic solvent in the ceramic green sheet slurry is set according to the type of polyvinyl acetal resin used, and is not particularly limited, but if it is too small, it is difficult to exhibit the solubility required for kneading. Also, if it is too large, the viscosity of the ceramic green sheet slurry composition becomes too low, which may cause poor handling when producing a ceramic green sheet. For this reason, the content of the organic solvent is preferably 20% by weight or more and 80% by weight or less.
[0044] The ceramic powder includes powders of oxides or non-oxides of metals or non-metals used in the manufacture of ceramics. The composition of these powders may be a single composition, a compound state, or a mixture. The constituent elements of the metal oxide or non-oxide may be a single element or a plurality of elements, both as cations and anions, and may further include additives added to improve the properties of the oxide or non-oxide. Specific examples of the oxides or non-oxides include oxides, carbides, nitrides, borides, and sulfides of Li, K, Mg, B, Al, Si, Cu, Ca, Sr, Ba, Zn, Cd, Ga, In, Y, lanthanides, actinides, Ti, Zr, Hf, Bi, V, Nb, Ta, W, Mn, Fe, Co, Ni, etc. In addition, specific oxide powders containing multiple metal elements, usually called double oxides, can be classified based on their crystal structure as follows: those with a perovskite structure include NaNbO3, SrZrO3, PbZrO3, SrTiO3, BaZrO3, PbTiO3, BaTiO3, etc.; those with a spinel structure include MgAl2O4, ZnAl2O4, CoAl2O4, NiAl2O4, MgFe2O4, etc.; those with an ilmenite structure include MgTiO3, MnTiO3, FeTiO3, etc.; and those with a garnet structure include GdGa5O4, GdGa5O5, etc. 12 , Y6Fe5O 12 Among these, the modified polyvinyl acetal resin of the present invention exhibits high properties when mixed with BaTiO3 powder in a ceramic green sheet.
[0045] The average particle size of the ceramic powder is not particularly limited, but for example, for producing a thin ceramic green sheet (thickness 5 μm or less), it is preferably 0.5 μm or less.
[0046] The above-mentioned slurry for ceramic green sheets may contain other resins such as polyvinyl acetal resins other than the polyvinyl acetal resin of the present invention, acrylic resins, ethyl cellulose, etc., within the range that does not impair the effects of the present invention. In such a case, the content of the polyvinyl acetal resin of the present invention relative to the total binder resins is preferably 50% by weight or more.
[0047] The above-mentioned slurry for the ceramic green sheet may contain, as necessary, a dispersant, an antioxidant, an ultraviolet absorber, a surfactant, a filler, etc., and in some cases, a small amount of other resin such as an acrylic resin or a urethane resin may be added.
[0048] The method for producing the slurry for the ceramic green sheet is not particularly limited, and examples thereof include a method in which the polyvinyl acetal resin of the present invention, an organic solvent, a ceramic powder, and various additives added as necessary are mixed using various mixers such as a ball mill, a blender mill, and a three-roll mill.
[0049] After the slurry for the ceramic green sheet is applied, the slurry is heated and dried to obtain a ceramic green sheet. The ceramic green sheets can be used to manufacture ceramic electronic components. For example, the ceramic electronic components can be manufactured by carrying out a step of applying a paste for electrode layers to the surfaces of the ceramic green sheets, and a step of stacking the ceramic green sheets on which the electrode layers have been formed, and heat-pressing the stack to obtain a laminate, followed by degreasing and firing the laminate.
[0050] The method for applying the slurry composition for ceramic green sheets is not particularly limited, and examples thereof include methods using a roll coater, a die coater, a curtain coater, etc. As for other specific methods, conventionally known methods can be used.
[0051] The ceramic electronic components are not particularly limited, and examples thereof include multilayer ceramic capacitors, multilayer ceramic inductors, capacitors, piezoelectric actuators, multilayer varistors, multilayer thermistors, EMI filters, aluminum nitride multilayer substrates, alumina multilayer substrates, etc. Such multilayer ceramic capacitors also constitute the present invention.
[0052] The method for producing a ceramic electronic component includes a step of applying a paste for electrode layers to the surfaces of the ceramic green sheets. The electrode layer paste can be obtained by dissolving, for example, polyvinyl acetal resin, ethyl cellulose, acrylic resin, etc. as a binder resin in an organic solvent and dispersing conductive powder, etc. These resins may be used alone or in combination of two or more. The electrode layer paste containing polyvinyl acetal resin is preferred because it exhibits excellent adhesion to the ceramic green sheet in the heat-pressing step.
[0053] In the method for producing a ceramic electronic component, the above-mentioned ceramic green sheets having electrode layers formed thereon are produced, and then similarly produced ceramic green sheets having electrode layers formed thereon are stacked and heated and pressed to obtain a laminate, which is then degreased and fired, thereby obtaining a multilayer ceramic electronic component in which problems such as sheet attack and cracks are solved. The above-mentioned heat-pressure bonding step and the steps of degreasing and firing the laminate are not particularly limited, and conventionally known methods can be used. Effect of the Invention
[0054] According to the present invention, it is possible to provide a polyvinyl acetal resin, a slurry for a ceramic green sheet, a ceramic green sheet, and a multilayer ceramic capacitor that can obtain a ceramic green sheet having high mechanical strength and suitable surface roughness and can fabricate a multilayer ceramic capacitor with excellent reliability. [Brief description of the drawings]
[0055] [Figure 1] 2 is an example of an IR absorption spectrum obtained by measuring the IR absorption spectrum of the polyvinyl acetal resin of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0056] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0057] Example 1 3000g of pure water was added to 300g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 99.1 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled at 1°C / min and held at 17°C for 1 hour to cool. The temperature was then raised again to 50°C at 0.5°C / min, and 220g of hydrochloric acid with a concentration of 35% by weight and 180g of n-butyl aldehyde were added thereto and held for 6 hours to carry out an acetalization reaction [reaction step]. The mixture was then neutralized, washed with water and dried by a conventional method to obtain a white powder of polyvinyl acetal resin.
[0058] (Preparation of ceramic green sheets) 2 parts by weight of the obtained polyvinyl acetal resin and 2 parts by weight of dioctyl phthalate (DOP) were added to 96 parts by weight of an ethanol / toluene mixed solvent (weight ratio 1:1) and dissolved with stirring to prepare a resin solution. In addition, 3 parts by weight of polyvinyl acetal resin "BL-1" (manufactured by Sekisui Chemical Co., Ltd.) was added to 40 parts by weight of an ethanol / toluene mixed solvent (weight ratio 1:1) and dissolved by stirring. Next, 100 parts by weight of barium titanate powder (manufactured by Sakai Chemical Industry Co., Ltd., BT01) was added and stirred for 180 minutes with a bead mill (Ready Mill manufactured by Imex Co., Ltd.) to prepare an inorganic dispersion. The above resin solution (100 parts by weight) was added to the inorganic dispersion obtained and stirred with a bead mill to obtain a slurry composition. During stirring, sampling was performed every 5 minutes, and 0.1 parts by weight of the obtained slurry composition was added to 10 parts by weight of an ethanol / toluene mixed solvent (weight ratio 1:1), and stirred with an ultrasonic disperser (US-303, manufactured by SND Co., Ltd.) to prepare a dispersion evaluation solution. The particle size distribution was measured using a laser diffraction particle size distribution meter (LA-910, manufactured by Horiba, Ltd.), and stirring was stopped when the D50 value of the particle size distribution reached 1.0 μm. The obtained slurry composition was applied onto a release-treated PET film using a coater so that the thickness after drying would be 20 μm, and then the film was dried by heating to prepare a ceramic green sheet.
[0059] Example 2 3000g of pure water was added to 300g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 99.2 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled at 1°C / min and then held at 10°C for 1 hour to cool. The temperature was then raised again to 50°C at 0.5°C / min, and 220g of hydrochloric acid with a concentration of 35% by weight and 180g of n-butyl aldehyde were added thereto and held for 6 hours to carry out an acetalization reaction [reaction step]. The mixture was then neutralized, washed with water and dried by a conventional method to obtain a white powder of polyvinyl acetal resin. A ceramic green sheet was produced in the same manner as in Example 1, except that the obtained polyvinyl acetal resin was used.
[0060] Example 3 3000g of pure water was added to 300g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 99.2 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled at 1°C / min and then held at 10°C for 1 hour to cool. The temperature was then raised again to 55°C at 0.5°C / min, and 220g of hydrochloric acid with a concentration of 35% by weight and 180g of n-butyl aldehyde were added thereto and held for 6 hours to carry out an acetalization reaction [reaction step]. The mixture was then neutralized, washed with water and dried by a conventional method to obtain a white powder of polyvinyl acetal resin. A ceramic green sheet was produced in the same manner as in Example 1, except that the obtained polyvinyl acetal resin was used.
[0061] Example 4 3000g of pure water was added to 300g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 99.2 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled at 1°C / min and held at 17°C for 1 hour to cool. The temperature was then raised again to 55°C at 0.5°C / min, and 220g of hydrochloric acid with a concentration of 35% by weight and 180g of n-butyl aldehyde were added thereto and held for 6 hours to carry out an acetalization reaction [reaction step]. The mixture was then neutralized, washed with water and dried by a conventional method to obtain a white powder of polyvinyl acetal resin. A ceramic green sheet was produced in the same manner as in Example 1, except that the obtained polyvinyl acetal resin was used.
[0062] Example 5 3000g of pure water was added to 300g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 99.4 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled at 1°C / min and then held at 17°C for 3 hours to cool. The temperature was then raised again to 50°C at 0.5°C / min, and 220g of hydrochloric acid with a concentration of 35% by weight and 180g of n-butyl aldehyde were added thereto and held for 6 hours to carry out an acetalization reaction [reaction step]. The mixture was then neutralized, washed with water and dried by a conventional method to obtain a white powder of polyvinyl acetal resin. A ceramic green sheet was produced in the same manner as in Example 1, except that the obtained polyvinyl acetal resin was used.
[0063] Example 6 3000g of pure water was added to 300g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 99.1 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled at 1°C / min and then held at 10°C for 1 hour to cool. The temperature was then raised again to 50°C at 0.5°C / min, and 220g of hydrochloric acid with a concentration of 35% by weight and 180g of n-butyl aldehyde were added thereto and held for 3 hours to carry out an acetalization reaction [reaction step]. The mixture was then neutralized, washed with water and dried by a conventional method to obtain a white powder of polyvinyl acetal resin. A ceramic green sheet was produced in the same manner as in Example 1, except that the obtained polyvinyl acetal resin was used.
[0064] Comparative Example 1 3000g of pure water was added to 300g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 99.1 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. This solution was not cooled below the reaction temperature, but was cooled to 50°C. Next, 220g of hydrochloric acid with a concentration of 35% by weight and 180g of n-butyl aldehyde were added to the mixture, and the mixture was held for 6 hours to carry out an acetalization reaction [reaction step]. After that, the mixture was neutralized, washed with water, and dried by a conventional method to obtain a white powder of polyvinyl acetal resin. A ceramic green sheet was produced in the same manner as in Example 1, except that the obtained polyvinyl acetal resin was used.
[0065] Comparative Example 2 3000g of pure water was added to 300g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 99.4 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled at 1°C / min and then held at 23°C for 1 hour to cool. The temperature was then raised again to 55°C at 0.5°C / min, and 220g of hydrochloric acid with a concentration of 35% by weight and 180g of n-butyl aldehyde were added thereto and held for 6 hours to carry out an acetalization reaction [reaction step]. The mixture was then neutralized, washed with water and dried by a conventional method to obtain a white powder of polyvinyl acetal resin. A ceramic green sheet was produced in the same manner as in Example 1, except that the obtained polyvinyl acetal resin was used.
[0066] Comparative Example 3 3000g of pure water was added to 300g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 99.0 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled at 1°C / min and then held at 17°C for 1 hour to cool. The temperature was then raised again to 40°C at 0.5°C / min, and 220g of hydrochloric acid with a concentration of 35% by weight and 180g of n-butyl aldehyde were added thereto and held for 6 hours to carry out an acetalization reaction [reaction step]. The mixture was then neutralized, washed with water and dried by a conventional method to obtain a white powder of polyvinyl acetal resin. A ceramic green sheet was produced in the same manner as in Example 1, except that the obtained polyvinyl acetal resin was used.
[0067] Comparative Example 4 3000g of pure water was added to 300g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 99.2 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled at 1°C / min and then cooled by holding at 5°C for 1 hour. The temperature was then raised again to 50°C at 0.5°C / min, and 220g of hydrochloric acid with a concentration of 35% by weight and 180g of n-butyl aldehyde were added thereto and held for 6 hours to carry out an acetalization reaction [reaction step]. The mixture was then neutralized, washed with water and dried by a conventional method to obtain a white powder of polyvinyl acetal resin. A ceramic green sheet was produced in the same manner as in Example 1, except that the obtained polyvinyl acetal resin was used.
[0068] Comparative Example 5 3000g of pure water was added to 300g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 99.1 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled at 1°C / min and then held at 10°C for 1 hour to cool. The temperature was then raised again to 65°C at 0.5°C / min, and 220g of hydrochloric acid with a concentration of 35% by weight and 180g of n-butyl aldehyde were added and held for 6 hours to carry out an acetalization reaction [reaction step]. The mixture was then neutralized, washed with water and dried by a conventional method to obtain a white powder of polyvinyl acetal resin. A ceramic green sheet was produced in the same manner as in Example 1, except that the obtained polyvinyl acetal resin was used.
[0069] (evaluation) The polyvinyl acetal resins and ceramic green sheets obtained in the Examples and Comparative Examples were evaluated as follows. The results are shown in Table 1.
[0070] (1) Evaluation of polyvinyl acetal resin (1-1) Amount of acetal groups, hydroxyl groups, and acetyl groups The polyvinyl acetal resin thus obtained was analyzed using an AV400 spectrometer (manufactured by Bruker Corporation). 1 H-NMR measurement was carried out, and the amounts of acetal groups, hydroxyl groups, and acetyl groups were calculated. The obtained polyvinyl acetal resin was dissolved in DMSO-D6 to a concentration of 1.6% by weight to prepare a measurement solution. 1 H-NMR measurements were carried out at 80 °C.
[0071] (1-2)z average molecular weight (THFMz, NMPMz) measurement The obtained polyvinyl acetal resin was dissolved in tetrahydrofuran (THF) at a concentration of 0.2% by weight, passed through a PTFE filter with a pore size of 0.45 μm, and measured using a GPC device HLC-8220 (manufactured by Tosoh Corporation) with THF as the mobile phase, a differential refractive index detector Bryce type double pass (manufactured by Tosoh Corporation) as the detector, and a TSKgel Super HZM-H (manufactured by Tosoh Corporation) as the column at a flow rate of 0.35 mL / min. The obtained measurement results were calibrated using a molecular weight calibration curve prepared using a monodisperse polystyrene standard sample, and the z-average molecular weight THFMz was obtained. Similarly, the obtained polyvinyl acetal resin was dissolved in N-methylpyrrolidone (NMP) at a concentration of 0.2% by weight, passed through a PTFE filter with a pore size of 0.45 μm, and measured using a GPC device GPC-101 (Shodex Co., Ltd.), NMP as the mobile phase, a differential refractive index detector RI-715 (Shodex Co., Ltd.) as the detector, and an LF-804 (Shodex Co., Ltd.) as the column at a flow rate of 0.5 mL / min. The obtained measurement results were calibrated using a molecular weight calibration curve prepared using a monodisperse polystyrene standard sample, and the z-average molecular weight NMPMz was obtained. "THFMz-NMPMz" was calculated from the obtained THFMz and NMPMz.
[0072] (1-3)IR Absorption Spectrum The obtained polyvinyl acetal resin was dissolved in a 1:1 ethanol / toluene mixed solution, and then coated on a PET film. -1 The film thickness of the measurement sample was adjusted so that the minimum transmittance of the peak appearing around the wavelength of the sample was 20%, and a polyvinyl acetal resin sheet was obtained. The IR absorption spectrum of the obtained polyvinyl acetal resin sheet was measured at 20°C using an infrared spectrophotometer (HORIBA, FT-720). The measurement results showed that the IR absorption spectrum of the obtained polyvinyl acetal resin sheet was 0.01 to 0.05 at a wave number of 3050 to 3750 cm. -1 A baseline was drawn for the peaks that appeared within the range, and peak analysis was performed on the data corrected so that the transmittances at both ends of the peak were 100%, and the minimum transmittance X, transmittance a, and peak wavenumbers A and B were measured. 1 The hydroxyl group amount calculated by H-NMR measurement was used to calculate the hydroxyl group amount conversion wavenumber width (cm -1 / mol%)=[(BA) / amount of hydroxyl groups] was calculated. Also, 1 The acetal group amount determined by H-NMR measurement was used to calculate the hydroxyl group-acetal group amount conversion wavenumber width (cm -1 / mol%)=[(BA) / amount of hydroxyl groups / amount of acetal groups] was calculated.
[0073] (1-4) Viscosity measurement The obtained polyvinyl acetal resin was dissolved in a 1:1 mixed solution of ethanol and toluene to a concentration of 5% by mass to prepare a sample for viscosity measurement. The viscosity of the obtained sample for viscosity measurement was measured using a B-type viscometer at a solution temperature of 20°C. The B-type viscometer used was a TVB-10 viscometer (manufactured by Toki Sangyo Co., Ltd.), and the measurements were performed with the following rotation speeds and rotors: Examples 1 to 6, Comparative Examples 1 to 5: Rotational speed 30 rpm, SPINDLE No. M1
[0074] (2) Evaluation of ceramic green sheets (2-1) Tensile modulus The tensile modulus (MPa) of the obtained ceramic green sheets was measured at a tension speed of 20 mm / min using a tensile tester (AUTOGRAPH AGS-J, manufactured by Shimadzu Corporation) in accordance with JIS K 7113, and evaluated according to the following criteria. A: Tensile modulus of elasticity is 1150MPa or more B: Tensile modulus of elasticity is 1090MPa or more and less than 1150MPa C: Tensile modulus less than 1090MPa
[0075] (2-2) Surface roughness The ten-point average roughness (Rz) of the obtained ceramic green sheets was measured in accordance with JIS B 0601 (1994) and evaluated according to the following criteria. A: Rz is 0.27μm or less B: Rz is over 0.27μm and 0.37μm or less C: Rz is over 0.37 μm
[0076] [Table 1] [Industrial Applicability]
[0077] According to the present invention, it is possible to provide a polyvinyl acetal resin, a slurry for a ceramic green sheet, a ceramic green sheet, and a multilayer ceramic capacitor that can obtain a ceramic green sheet having high mechanical strength and suitable surface roughness and can fabricate a multilayer ceramic capacitor with excellent reliability.
Claims
1. In GPC measurement using a differential refractive index detector, the z-average molecular weight (THFMz) obtained by using THF as a mobile phase and the z-average molecular weight (NMPMz) obtained by using NMP as a mobile phase satisfy the following formula (1), and In the IR absorption spectrum measured by an infrared spectrophotometer, the wave number is 3050 to 3750 cm -1 When the minimum transmittance of the peak within the range is X (%), among the wave numbers showing the transmittance a (%) that satisfies [100-(100-X) / 2], the wave number on the low wave number side is A and the wave number on the high wave number side is B. 1 The hydroxyl group amount converted wavenumber width calculated by the following formula (2) using the hydroxyl group amount measured by H-NMR is 8.3 to 9.4, A polyvinyl acetal resin having a hydroxyl group content of 18 mol % or more and 40 mol % or less and an acetyl group content of 0.1 mol % or more and 20 mol % or less. THFMz-NMPMz<470000 (1) Hydroxyl group amount converted wave number width (cm -1 / mol%) = [(B - A) / amount of hydroxyl groups] (2)
2. The above A is 3275 cm -1 Above, 3305cm -1 2. The polyvinyl acetal resin according to claim 1, wherein:
3. The above A, B and 1 3. The polyvinyl acetal resin according to claim 1, wherein the hydroxyl group-acetal group amount converted wavenumber width calculated by the following formula (3) using the hydroxyl group amount and acetal group amount measured by H-NMR is 0.120 to 0.135: Hydroxyl group acetal group amount converted wave number width (cm -1 / mol% / mol%)=[(B−A) / amount of hydroxyl groups / amount of acetal groups] (3)
4. 3. The polyvinyl acetal resin according to claim 1, wherein a 5 mass% solution of the polyvinyl acetal resin in a 1:1 mixed solvent of ethanol and toluene has a solution viscosity of 64 mPa s or more and 2,000 mPa s or less, as measured using a B-type viscometer at a solution temperature of 20°C.
5. A slurry for a ceramic green sheet, comprising the polyvinyl acetal resin according to claim 1 or 2, an organic solvent, and ceramic powder.
6. A ceramic green sheet obtained by using the slurry for ceramic green sheet according to claim 5.
7. A multilayer ceramic capacitor obtained by using the ceramic green sheet according to claim 6.
Citation Information
Patent Citations
Manufacturing method of polyvinyl butyral film
CN106398071A
Binder for ceramic forming comprising vinyl acetal polymer and ceramic green sheet containing the same
JP2010001488A
Polyvinyl acetal resin for ceramic green sheet, slurry composition, ceramic green sheet, and laminate ceramic condenser
JP2011236304A
JPP7432051B
Polyvinyl acetal resin, slurry composition prepared therefrom, ceramic green sheet, and multilayer ceramic capacitor
WO2012023517A1